2023
DOI: 10.1007/s12144-023-04606-0
|View full text |Cite
|
Sign up to set email alerts
|

The serial mediation effect of prospective imagery vividness and anxiety symptoms on the relationship between perceived stress and depressive symptoms among Chinese vocational college students during the COVID-19 pandemic

Abstract: The mental health of vocational college students has been neglected during the COVID-19 pandemic. Prospective imagery may play a role in the relationships among stress, anxiety and depression. This study aimed to survey the mental health of Chinese vocational college students and explore the mediation effect of prospective imagery vividness and anxiety symptoms on the relationship between perceived stress and depressive symptoms. A total of 2, 381 vocational college students ( M age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…5 Liu et al’s research of 2381 vocational school students in China showed that the prevalence of student stress, anxiety and depressive symptoms were 55.7%, 33.2% and 53.5%, respectively. 6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Liu et al’s research of 2381 vocational school students in China showed that the prevalence of student stress, anxiety and depressive symptoms were 55.7%, 33.2% and 53.5%, respectively. 6 …”
Section: Introductionmentioning
confidence: 99%
“…5 Liu et al's research of 2381 vocational school students in China showed that the prevalence of student stress, anxiety and depressive symptoms were 55.7%, 33.2% and 53.5%, respectively. 6 A personality trait is a relatively stable personality state formed by a person that reflects that person's attitude towards things. A large body of evidence suggests that personality can be seen as an emergent property of the response to emotional experience.…”
Section: Introductionmentioning
confidence: 99%